Multimodal critical discourse analysis as ethical praxis. Issue 2 (15th March 2018) - Roderick, Ian
ABSTRACT: Critical Discourse Studies (CDS) positions itself as a critical, transformative practice that seeks to expose the ways in which discourse is able to constitute social, political, economic, gendered, racial, and sexual inequalities as normal and unremarkable. In this respect, CDS is an expressly political and therefore ethical project. Nevertheless, this article posits that, quite remarkably, the ethical frameworks that guide CDS have remained largely under-theorized and taken for granted. Accordingly, this paper seeks to contribute to this much-needed area of theoretical inquiry by offering a brief discussion of how CDS has tended to define its own criticality and identifies three problems that emerge from how CDS practitioners have tended to formulate the praxis of critique: namely, the tendency to conceive of CDS as a demystificatory practice, the implicit logocentrism of modeling ethics upon the Habermasian Ideal Speech Situation ( ISS ), and finally, the deontological nature of discourse ethics. Each of the three problems is discussed in relation to a brief multimodal critical discourse analysis of three online employer profile videos. As such, the study is offered to demonstrate not only the analytical strength of multimodal analysis but also the political-ethical relations beyond Discourse Ethics that are immanent in such analyses.